Multielement, Cl-, CH4, NH4, DIC concentrations and δ2H, δ18O, δ7Li, δ34S, 87Sr/86Sr, δ13C-DIC composition of groundwater, seawater and pockmark porewater from Hanko SGD site, Finland - Joonas J Virtasalo; Cátia Milene Ehlert von Ahn; Tom Jilbert; Hermann W Bange; Anna Jenner; Michael Ernst Böttcher; Samrit Luoma; Yann Lahaye (PANGAEA, 2022)
This dataset contains the concentrations of 34 elements, chloride, methane, ammonium, and dissolved inorganic carbon, as well as δ2H, δ18O, δ7Li, δ34S, 87Sr/86Sr and δ13C-DIC in groundwater and seawater samples as well as in sediment porewater samples from pockmarks associated with submarine groundwater discharge (SGD) at the Hanko cape in Finland, northern Baltic Sea. The groundwater samples were collected onshore from an observation well using a suction pump and from a water intake well. The seawater and pockmark porewater samples were collected from the research vessel Geomari of the Geological Survey of Finland (GTK). The seawater samples were collected onboard from 2 m, 6 m, and 10 m below sea surface at the pockmark locations using a Limnos water sampler. The porewater samples were extracted using Rhizons at 1-2 cm vertical intervals from sediment cores that were collected from the pockmarks at 11 m water depth. Multielement composition of the seawater, groundwater and porewater samples were analyzed using inductively coupled plasma optical emission and mass spectrometry (ICP-OES and ICP-MS). Ca, Fe, K, Mg, Mn, Na, and S were analysed by ICP-OES, whereas Ag, Al, As, B, Ba, Be, Bi, Cd, Co, Cr, Cu, I, Li, Mn, Mo, Ni, P, Pb, Rb, Sb, Se, Sr, Th, Tl, U, V, and Zn were analysed by ICP-MS. Major anions (Br, Cl, F, NO3 and SO4) were analyzed using ion chromatography. Alkalinity (as HCO3-), electrical conductivity, pH and KMnO4 consumption of the unfiltered and unpreserved groundwater samples were measured immediately upon arrival at the laboratory. Methane concentrations in the seawater, groundwater and porewater samples were determined by gas chromatography with flame ionization detector. Headspace CH4 concentrations were converted to total dissolved phase concentrations in the original porewater sample using Henry extquotesingles Law. δ13CDIC values were determined by means of continuous-flow isotope-ratio-monitoring mass spectrometry (CF-irmMS). The concentrations of NH4+ and PO4 were analyzed spectrophotometrically. Hydrogen and oxygen isotope ratios of the groundwater, seawater and porewater samples were analyzed by cavity ring down spectroscopy (CRDS). The isotope ratios are reported as deviation from the international VSMOW-standard. The uncertainty (2σ) of measurement is <0.1 extperthousand for oxygen analysis and <0.3 extperthousand for hydrogen analysis. For the determination of δ7Li, δ34S and 87Sr/86Sr, the elements were eluted from the groundwater, seawater and porewater samples by liquid column chromatography. The isotope ratios in the eluted samples were analyzed by multi-collector ICP-MS. The Li, S and Sr isotope ratios are reported against the LSVEC, NBS987 and CDT reference materials, respectively. The standard mean deviations of Li and S isotope determinations are +/- 0.32 and +/- 0.52 extperthousand, respectively. The mean 2SE of Sr isotope determinations is +/- 0.000015. In the dataset, The given extperthousand values are equivalent to mUr (milli Urey)